Morin protects gastric mucosa from nonsteroidal anti-inflammatory drug, indomethacin induced inflammatory damage and apoptosis by modulating NF-κB pathway - Sinha, Krishnendu; Sadhukhan, Pritam; Saha, Sukanya; Pal, Pabitra Bikash; Sil, Parames C. (Biochimica et biophysica acta, 2015)
Deregulation in prostaglandin (PG) biosynthesis, severe oxidative stress, inflammation and apoptosis contribute to the pathogenesis of nonsteroidal anti-inflammatory drug (NSAID)-induced gastropathy. Unfortunately, most of the prescribed anti-ulcer drugs generate various side effects. In this scenario, we could consider morin as a safe herbal potential agent against IND-gastropathy and rationalize its action systematically. Rats were pretreated with morin for 30 min followed by IND (48 mgkg(-1)) administration for 4 h. The anti-ulcerogenic nature of morin was assessed by morphological and histological analysis. Its effects on the inflammatory (MPO, cytokines, adhesion molecules), ulcer-healing (COXs, PGE(2)), and signaling parameters (NF-κB and apoptotic signaling) were assessed by biochemical, RP-HPLC, immunoblots, IHC, RT-PCR, and ELISA at the time points of their maximal changes due to IND administration. IND induced NF-κB and apoptotic signaling in rat's gastric mucosa. These increased proinflammatory responses, but reduced the antioxidant enzymes and other protective factors. Morin reversed all the adverse effects to prevent IND-induced gastric ulceration in a PGE2 independent manner. Also, it did not affect the absorption and/or primary pharmacological activity of IND. The gastroprotective action of morin is primarily attributed to its potent antioxidant nature that also helps in controlling several IND-induced inflammatory responses. For the first time, the study reveals a mechanistic basis of morin mediated protective action against IND-induced gastropathy. As morin is a naturally abundant safe antioxidant, future detailed pharmacokinetic and pharmacodynamic studies are expected to establish it as a gastroprotective agent.